ALTERNATIF SOLUSI AL-QUR`AN DALAM MENGATASI KEMISKINAN - Sulaiman -; Ilham Ali Hasan; Latifatun Nafisah (IAT IAIN Pontianak, 2022)
This article describes poverty and overcoming poverty in the Qur'an. The problem of poverty is an urgent matter in human life, especially in developing countries which have always been a problem in the welfare of the people. So this research was conducted looking at the point of view of the Qur'an looking at poverty in the community. This research is included in a descriptive qualitative research cluster with a literature study approach whose data sources are from the Qur'an, hadith books, journals that are in line with the research, as well as supporting books in research. Apart from the debate about poverty according to social experts and the sciences related to it in fact the Qur'an has explained the solution to poverty itself. The poverty discourse in the Qur'an aims to find solutions and innovations from the verses of the Qur'an so that they become a guide in the relationship between humans and humans. The solutions are the development of Human Resources, the use of Natural Resources and improvements in the government system, so that these three solutions are able to overcome poverty well.